Words of blessing in the Holy Quran (Journal of the College of Basic Education, 2023)
This research deals with the term (barak) in dictionaries, interpretations, and derivatives of this term in the Holy Qur’an and the noble Prophet’s Sunnah. The Qur’anic interpretations of these derivatives are presented. And the importance of blessing for man. The research sheds light on the sources of blessing and the reasons for its demise, as well as some blessed times and blessed places.